Beggar thy neighbor? On the competitiveness and welfare impacts of the EU's proposed carbon border adjustment mechanism. (March 2022) - Zhong, Jiarui; Pei, Jiansuo
Abstract: Curbing climate change is gaining increasing consensus globally. While many countries seek to set carbon prices, significant price dispersion and policy stringency continue to raise concerns about competitiveness. To address this issue, the EU has proposed a carbon border adjustment mechanism (CBAM), which aims to level the playing field by levying a carbon price on EU imports. In this paper, we estimate the competitiveness and welfare impacts of the EU CBAM, based on a refined multi-regional IO approach. We quantify changes in the value of exports to the EU market upon CBAM implementation for both EU members and non-EU economies. It is found that the EU CBAM will lead to a redistribution of competitiveness among countries and regions. Specifically, it is estimated that EU output would increase by 0.38 per cent while output in rest of the world decreases by 0.1 per cent in the short run, when CBAM is set at US100/tCO2 e. The burden is unevenly distributed among regions, with China, Russia and India bearing the most. Moreover, a deeper sub-national-level analysis on China shows that, given its pervasive domestic production network, income losses in landlocked provinces exceed their export losses, contrasting with the pattern for trade-exposed provinces. Highlights: EU has proposed a CBAM to address the competitiveness concerns. CBAM aims to level the playing field for products produced within and outside EU. The EU CBAM has significant redistribution effect both at country and sector level. The CBAM may reduce EU's competitiveness due to rising production costs in long run. Within China, income losses in landlocked provinces would exceed their export losses.